Low-volume enrichment method supports high throughput bacteriophage screening and isolation from wastewater. - Patrick O Kenney; Oscar G Gómez-Duarte (PLoS ONE, 2024)
Bacteriophage therapy is a rapidly growing field of study. Narrow host ranges, bacterial resistance, and limited antibiotic availability make lytic phages a feasible therapeutic potential. Phage discovery, a critical step in developing phage therapy, is a pathway to accessible treatment. This has always been a laborious, time-consuming and resource-intensive process. In this paper, we describe a 96-well plate low-volume bacteriophage enrichment method with concentrated environmental sources to rapidly discover and isolate phages targeting multiple organisms simultaneously. Samples from natural water sources, wastewater influent, and activated sludge were tested in large volume enrichment cultures and low-volume 96-well plate format. Each plate has the capacity to run as many as 48 different combinations with multiple bacterial hosts. The time to identify the presence of phage in a sample was 5 to 10 hours in the low-volume format versus a minimum of 2 days in the traditional enrichment method. The labor and expense involved also favor the 96-well plate format. There was some loss of discovered phages using this technique, primarily targeting bacterial species less prevalent in the environment. This is an easily modifiable method that is amenable to automation and a variety of potential phage sources.